В стране перепутанных сказок - Биллевич Виктор Всеволодович (Новые сказочные повести, 2007)
Экземпляры: М/а ДБ (20081118) / Инвентарный номер: 92028 / Цена: 105.16 / Авт.знак: Б 61 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6